On the performance of hybrid PV/unitized regenerative fuel cell system in the tropics - Dihrab S.; Khatib T.; Sopian K.; Al-Ani H.; Zaidi S.H. (Hindawi Limited, 2023)
Solar hydrogen system is a unique power system that can meet the power requirements for future energy demands. Such a system uses the hydrogen as the energy carrier, which produces energy through the electrolyzer with assistance of the power from the PV during the sunny hours, and then uses stored hydrogen to produce energy through the fuel cell after sunset or on cloudy days. The current study has used premanufactured unitized regenerative fuel cells in which the electrolyzer and the fuel cell function within one cell at different modes. The system components were modeled and the one-day real operational and simulated data has been presented and compared. The measured results showed the ability of the system to meet the proposed load, and the total efficiency was about 4.5%. 2012 Salwan Dihrab et al.